2018
DOI: 10.26905/jkdp.v22i4.1994
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Profit Sharing Financing and Zakat Distribution Based on CAMEL Analysis

Abstract: The rapid development of Islamic banking has many positive impacts, but on the other hand, the development also demands the readiness of sharia banking in meeting the soundness level standard set by the regulator. This study aimed to integrate the two methods of measurement of Islamic financial institutions, the CAMEL method and maqasidsharia method. How far the ability of CAMEL, macro and general measurement, in measuring the variables on the maqasid sharia. This research used panel data model and analyzed fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Many factors can influence banks in channeling their financing, both internal and external factors. There are several ways to identify factors that can affect profit-sharing financing as has been done by previous researchers, including the influence of mudharabah deposits (Kiswanto, 2013;Pramono, 2013;Riyanto, 2016), the influence of non-performing financing (Arnan & Kurniawasih, 2014;Kurniawanti & Zulfikar, 2014;Annisa & Yaya, 2015;Destiana, 2016;Jamilah, 2016;Kalkarina et al, 2016;Riyanto, 2016;Murni et al, 2018;Ispad, 2019;Nastiti & Kasri, 2019), equivalent rate (Kiswanto, 2013;Pramono, 2013;Kurniawanti & Zulfikar, 2014;Riyanto, 2016), efficiency (Jamilah, 2016;Nastiti & Kasri, 2019), economic growth (Ayyubi et al, 2017;Anwar et al, 2020;Hafizh et al, 2020) and inflation (Priyanto et al, 2016;Nastiti & Kasri, 2019;Mubarok et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many factors can influence banks in channeling their financing, both internal and external factors. There are several ways to identify factors that can affect profit-sharing financing as has been done by previous researchers, including the influence of mudharabah deposits (Kiswanto, 2013;Pramono, 2013;Riyanto, 2016), the influence of non-performing financing (Arnan & Kurniawasih, 2014;Kurniawanti & Zulfikar, 2014;Annisa & Yaya, 2015;Destiana, 2016;Jamilah, 2016;Kalkarina et al, 2016;Riyanto, 2016;Murni et al, 2018;Ispad, 2019;Nastiti & Kasri, 2019), equivalent rate (Kiswanto, 2013;Pramono, 2013;Kurniawanti & Zulfikar, 2014;Riyanto, 2016), efficiency (Jamilah, 2016;Nastiti & Kasri, 2019), economic growth (Ayyubi et al, 2017;Anwar et al, 2020;Hafizh et al, 2020) and inflation (Priyanto et al, 2016;Nastiti & Kasri, 2019;Mubarok et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies found different results regarding the factors that affect the size of profit-sharing financing in Islamic banks, as shown by Annisa & Yaya (2015), Riyanto (2016), and Ispad (2019), which found that Non-Performing Financing (NPF) has a negative effect on profit-sharing financing, while Destiana (2016), Jamilah (2016) and Nastiti & Kasri (2019) found that NPF has a positive effect on funding profit-sharing. On the other hand Giannini (2013), Arnan & Kurniawasih (2014), Kurniawanti & Zulfikar (2014), Kalkarina et al (2016) and Murni et al (2018) revealed that NPF has no effect on profit-sharing financing. In addition, there are differences in the results of research conducted by Giannini (2013), Kiswanto (2013), Kurniawanti & Zulfikar (2014), and Annisa & Yaya (2015), which found that equivalent rate (profit-sharing rates) has an effect on profit-sharing financing, while Pramono (2013) and Riyanto (2016) found that the profitsharing rate has no impact on funding profit-sharing.…”
Section: Introductionmentioning
confidence: 99%
“…According to several previous studies, the development of total Islamic bank financing is affected by microeconomic and macroeconomic factors. Several microeconomic factors, including non-performing financing (Nastiti & Kasri, 2019), operational efficiency (Nastiti & Kasri, 2019), liquidity (Murni et al, 2018;Nastiti & Kasri, 2019), and profitability (Murni et al, 2018;Nastiti & Kasri, 2019). While macroeconomic factors that affect financing growth include: economic growth (Anwar et al, 2020;Ayyubi et al, 2017;Hafizh et al, 2020), inflation (Mubarok et al, 2020;Nastiti & Kasri, 2019), interest rates (Hafizh et al, 2020;Mubarok et al, 2020), the composite stock price index (Hafizh et al, 2020), and exchange rates (Mubarok et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The microeconomic and macroeconomic factors that affect the growth of equity-based financing include: third party funds (Annisa & Yaya, 2015;Arnan & Kurniawasih, 2014;Destiana, 2016;Furqaini & Yaya, 2016;Giannini, 2013;Ispad, 2019;Jamilah, 2016;Priyanto et al, 2016), mudharabah deposits (Kiswanto, 2013;Pramono, 2013;Riyanto, 2016), nonperforming financing (Annisa & Yaya, 2015;Arnan & Kurniawasih, 2014;Destiana, 2016;Ispad, 2019;Jamilah, 2016;Kalkarina et al, 2016;Kurniawanti & Zulfikar, 2014;Murni et al, 2018;Nastiti & Kasri, 2019;Riyanto, 2016), equivalent rate (Kiswanto, 2013;Kurniawanti & Zulfikar, 2014;Pramono, 2013;Riyanto, 2016), operational efficiency (Jamilah, 2016;Nastiti & Kasri, 2019), liquidity (Furqaini & Yaya, 2016;Giannini, 2013;Jamilah, 2016;Ningsih, 2017;Priyanto et al, 2016;Syu'la et al, 2021), economic growth (Hafizh et al, 2020), inflation (Mubarok et al, 2020;Priyanto et al, 2016), and interest rates (Hafizh et al, 2020;Mubarok et al, 2020;Priyanto et al, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to several previous studies, the growth of total Islamic bank financing is influenced by microeconomic and macroeconomic factors. Several microeconomic factors, including non-performing financing (Nastiti & Kasri, 2019), operational efficiency (Nastiti & Kasri, 2019), liquidity (Murni et al, 2018;Nastiti & Kasri, 2019), and profitability (Murni et al, 2018;Nastiti & Kasri, 2019). Meanwhile, macroeconomic factors that affect financing growth include economic growth (Anwar et al, 2020;Ayyubi et al, 2017;Hafizh et al, 2020), inflation (Mubarok et al, 2020;Nastiti & Kasri, 2019), interest rate (Hafizh et al, 2020;Mubarok et al, 2020), composite stock price index (Hafizh et al, 2020), and exchange rate (Mubarok et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%